Internal Communication Function of Madrasah Principal (Communication Analysis at Elementary Education Institutions) - Qomaruddin Lubis; Mesiono Mesiono; Azhar Azhar; Faisal Faisal; Abd. Kholid (Jurnal Basicedu, 2023)
The communication pattern applied by the madrasa head becomes a crucial aspect in determining the optimal level of teacher performance. This study aims to analyze the function of implementing the internal communication of the madrasa head in improving the performance of teachers at Madrasah Tsanawiyah At-Tibyan Deli Serdang. This study used a qualitative approach with an analytical descriptive study method. Collecting data using the method of observation, interviews and document study. Furthermore, analyzed using data reduction techniques, data presentation and drawing conclusions. Test the validity of the data using data triangulation techniques. The results of this study concluded that the internal communication of the madrasah head with the madrasah committee and other personnel in improving the performance of Madrasah Tsanawiyah At-Tibyan Deli Serdang teachers turned out to be well established through internal communication carried out by the madrasah head with the madrasah committee. The internal communication built by the head of the madrasa to the madrasa committee is not only limited to downward communication but the head of the madrasa also builds upward communication with the madrasa committee.